The influence of health education using educational videos about awareness of knowledge young women in SMP Negeri 1 Sawo, Sawo District, North Nias Regency in 2023 - Nasution, Herlia Sumardha; Fitriani, Fitriani; Telaumbanua, Ingat Kasih (Jurnal EduHealth, 2024)
Breast cancer is the main cause of death among all cancers experienced by women in Indonesia. Global Cancer Observatory data for 2018 shows that the incidence of cancer in Indonesia (136.2/100,000 population) is at number 8 in Southeast Asia. Breast cancer cases that occur in teenagers are thought to be due to lifestyle. One effort that can be done is to REALIZE.This study aims to determinepThe influence of health education using educational videos about REALIZE on the knowledge of young women at SMP Negeri 1 Sawo, Sawo District, North Nias Regency in 2023. This research is study Pre-Experimental Design is a one-group pretest-posttest design approach. This research was carried out from 21 August 2023 to 2 September 2023. The population was141 female students. Sampling usingsimple random samplingwith a total sample of 45 people. The research results showed that young women's knowledge about REALIZE before being given health education using educational videos at SMP Negeri 1 Sawothe majority are not good andThe majority of young women's knowledge about REALIZE after being given health education using educational videos at SMP Negeri 1 Sawo is good. Based on the results of the paired sample t-test, it was found that the p value = 0.001 <a = 0.05. The conclusion in this research is yesThe influence of health education using educational videos about REALIZE on the knowledge of young women at SMP Negeri 1 Sawo, Sawo District, North Nias Regency in 2023. Suggestions in this researchSMP Negeri 1 Sawo continues to provide ongoing education to SMP Negeri 1 Sawo students so they can optimize the prevention and early detection of breast cancer in adolescents through educational videos about REALIZE.